The rua whetu joint: Detail as origin - Treadwell, Jeremy (Interstices: Journal of Architecture and Related Arts, 2016)
This paper examines a key structural junction of the 19th century Māori wharenui, or meeting house. The joint is considered as a complex cultural and technical element of the house which contributed to both its structural and social coherence. The functional development of the waha paepae and the rua whetu junctions as compression joints will be examined in relation to their participation in the evolving structural system of the 19th century whare, particularly in respect to their increasing size and subsequent structural loads. Equally invested in the structural and geometrical implications of this junction is a set of cosmological relationships that were essential for the wider stability of the house. This paper will therefore consider the joint within the complexity of its origins, development and forms.